2016
DOI: 10.12659/ajcr.899754
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Intravenous Vitamin C Treatment of a Child with Neurofibromatosis Type 1 and Optic Pathway Glioma: A Case Report

Abstract: Patient: Male, 1Final Diagnosis: Optic gliomaSymptoms: Visual problemsMedication: —Clinical Procedure: Intravenous vitamin CSpecialty: OncologyObjective:Unusual clinical courseBackground:In neurofibromatosis type 1 (NF1) disease, the loss of the tumor suppressor function of the neurofibromin gene leads to proliferation of neural tumors. In children, the most frequently identified tumor is the optic pathway glioma.Case Report:We describe the case of a 5-year-old child who was diagnosed with NF1 and optic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…The median ascorbic acid dose was 260 mg/kg/day and ranged from 100 to 1,500 mg/kg/day. Similar to the systematic review on adult patients, the safety related to high dose ascorbic acid in children and neonates was very high with no adverse event associated with ascorbic acid reported (55)(56)(57)(58)(59)(60).…”
Section: Safety Of High-dose Ascorbic Acidmentioning
confidence: 75%
“…The median ascorbic acid dose was 260 mg/kg/day and ranged from 100 to 1,500 mg/kg/day. Similar to the systematic review on adult patients, the safety related to high dose ascorbic acid in children and neonates was very high with no adverse event associated with ascorbic acid reported (55)(56)(57)(58)(59)(60).…”
Section: Safety Of High-dose Ascorbic Acidmentioning
confidence: 75%
“…Since then, pharmacokinetic data have demonstrated that infusion results in supra-physiological plasma ascorbate levels that are not achievable by oral administration (226)(227)(228)(229). Case studies and small clinical trials continue to surface that suggest there may be circumstances under which high dose ascorbate infusion can provide a clinical benefit (230)(231)(232)(233)(234)(235)(236)(237)(238)(239).…”
Section: High Dose Ascorbate As Cancer Treatmentmentioning
confidence: 99%
“…A trend of improved overall survival was reported, but participant numbers were too small to determine statistical significance ( 240 ). Two case reports for the use of HDVC infusions in patients with glioma have also been reporting ( 237 , 246 ).…”
Section: High Dose Ascorbate As Cancer Treatmentmentioning
confidence: 99%
“…Nonetheless, a meta-analysis by Zhou et al indicated that vitamin C intake may help to diminish the chance of glioma incidence [ 126 ]. Moreover, several studies indicated that, in glioma patients, intravenous supplementation may successfully serve as an adjuvant tumor therapy and significantly increase survival, as well as reduce and stabilize the tumor [ 127 , 128 ].…”
Section: Vitamin C In Adjuvant Cancer Therapymentioning
confidence: 99%